Evaluation of drug adherence in patients with non-valvular atrial fibrillation according to geographic regions of Turkey: An analysis from NOAC-TR study - Emren, Volkan; Zoghi, Mehdi; Açıksarı, Gönül; Aslan, Abdullah; Çelebi, Barış; Bilgin, Murat; İnci, Sinan (My University, 2017)
Drug adherence to novel oral anticoagulants (NOAC) varied by countries and popuplations. As a result of NOAC-TR study, in Turkey, drug adhrence to NOACs is poor comparing to other real world studies. However it is not known whether there is a difference between geographic regions of Turkey in terms of NOAC adherence. In this study we aim to investigate the NOAC adherence in patients with non-valvular atrial fibrillation according to the geographic regions in Turkey Method: This cros-sectional study was designed as a subgroup study of NOAC-TR (Drug Adherence in patients with non valvular atrial fibrillation taking non-vitamin K antagonist oral anticoagulants in Turkey). A total of 2802 patients (59% female) taking NOAC (Dabigatran, apixaban, rivaroxaban) due to NVAF at least 3 months, were included. Morisky-8 item drug adherence scale was used. Patients were divided in 3 groups (high, moderate and low adherent) based on drug adherence Results: Of the patients 24% were adherent, 26% were moderate adhererent and 50% were low adherent to NOAC treatment. Drug adhrence was different between geographic regions (p<0,001). In post-hoc analysis low adherent rate was highest in Blacksea region (72% low adherent, 21% moderate adherent, 7% low adherent). Adherence rate was highest in Aegean (36% adherent, 26% moderate adherent 38%) and Marmara region (38% adherent, 28% moderate adherent 34% low adherent). Conclusion: NOAC adherence was different between geographic regions in Turkey
Keywords: Genel ve Dahili Tıp; Sağlık Politikaları ve Hizmetleri; Kalp ve Kalp Damar Sistemi